Notes on the biology and distribution of the tribe Agallissini in North America (Coleoptera: Cerambycidae: Cerambycinae) - Austin, Thomas; Heffern, Daniel; Gemmill, Robert; Raber, Brian; Quinn, Mike (Zootaxa, 2018)
New distributional records, new larval host records, various collecting notes, and observations are reported for the North American species of the tribe Agallissini LeConte, 1873 (Coleoptera: Cerambycidae: Cerambycinae): Agallissus lepturoides (Duponchel & Chevrolat, 1841), Osmopleura chamaeropis (Horn, 1893), and Zagymnus clerinus (LeConte, 1873). The species are illustrated and distribution maps are provided.